Case Report: Secondary Hemophagocytic Lymphohistiocytosis (sHLH) and Candida auris Fungemia in Post-acute COVID-19 Syndrome: A Clinical Challenge - Gautam, Sachin; Sharma, Gaurav; Singla, Sumeet; Garg, Sandeep (Frontiers in Medicine, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection causes a disease (COVID-19) with multisystem involvement. The world is now entering a phase of post COVID-19 manifestations in this pandemic. Secondary hemophagocytic lymphohistiocytosis (sHLH) is a life-threatening hyperinflammatory event triggered by viral infections, including SARS-CoV-2. Both Multisystem Inflammatory Syndrome-Adults (MIS-A) and Cytokine Storm Syndrome (CSS) are considered as close differentials of sHLH, and add to the spectrum of Post-Acute COVID-19 Syndrome (PACS). Here we are presenting the case of a middle-aged Asian gentleman who was initially discharged upon recovery from severe COVID-19 infection after 17 days of hospitalization to a private institute and later came to our hospital 13 days post-discharge. Here, he was diagnosed with sHLH, occurring as an extension of CSS, with delayed presentation falling within the spectrum of PACS. The diagnosis of sHLH was made holistically with HLH-2004 criteria. Our patient initially responded to Intravenous immunoglobulin (IVIG) and dexamethasone, later complicated by disseminated Candida auris infection and had a fatal outcome. Though many cases of HLH during active COVID-19 and a few cases post COVID-19 recovery have been reported, based on H-score, which has limitations as a diagnostic tool. We report the first case report of post-COVID-19 sHLH using HLH-2004 criteria, complicated by disseminated Candidemia emphasising that care of COVID-19 patients does not conclude at the time of hospital discharge. We highlight the importance of surveillance in the post-COVID phase for early detection of sHLH predisposing to fatal opportunistic infections (OIs) to improve clinical outcomes.